The Development Of Higher Education For Sustainable Development Model (HESD): Critical Success Factors, Benefits, And Challenges - Mad Ithnin Salleh; Nurul Fadly Habidin; Sharifah Zarina Syed Zakaria; Khairunneezam Mohd Noor (Human Resource Management Academic Research Society, 2024)
Indexed by ERA